Data privacy comparison using advanced encryption standard (AES) and data encryption standard (DES) / Hikma Farah Ali - Ali, Hikma Farah (2019)
Cryptography has wide ranges as it has the ability to handle different attacks. It has a set of security objectives to ensure the confidentiality of data. This changes the content of the data being sent to a readable form once received by the recipient and is converted back to its original form. Using this project for generated key for protect the file. The file is encrypted and using this key to decrypt it. In this study existing algorithm DES is a symmetric-key block cipher. DES creates 64 bit cipher text and produces 64-bit block of plaintext. As encryption and decryption of DES uses same cipher key by 56 bit. Proposed algorithm AES, has a different key sizes ,as 128,192 and 256. DES has weak keys. For avoiding the issues in DES, we propose, AES which is a stronger key schedule should prevent weak keys. In this project using the AES algorithm, it benefits to encryption and decryption and it avoids the time delay. Our aim is to safely to transfer the file for using the AES algorithm. Proposed algorithm has done by analysing the different time taken for both AES and DES , experiment was done by three different file sizes and also file types, such as text, image and voice to test the encryption and decryption time taken on existing algorithm DES and proposed algorithm, in conclusion, all the results of our propose algorithm shows AES takes lesser time compare to DES. Our propose also compare the key bit size of existing algorithm DES and Proposed algorithm AES. Finally our result show the AES has strong key compare to DES.